Competência clínica em pediatria: proposta de instrumentode avaliação discente no internato - Luiz Megale (2007)
The certification that graduated students are able to work in their professional careers with total competence is not only the responsibility from the education institution but also a requirement from the society. In medical education, the envolved competences constitute most of the time knowledge and complex abilities with different inter-relations between the development of ethical values, attitudes and behavior, all of them, essential to the future of professional practice. Medical students evaluation, therefore, must include a variety of tools related to specific aspects to allow the identification of the areas that need to be improved, in order to offer the society, a high quality of service. Although the medical school at Federal University of M.G. has reached, since 1975, the necessary tools and competences for the professional development, the evaluation process still tends more to cognitive contents acquisition. Clinical skills evaluation is made in an informal and private process by the professor, at the end of, the discipline, mainly based on the student behavior without clear criteria, which may cause a wrong evaluation and may be influenced by the halo effect. The clinical competence evaluation is an essential step in the medicine student formation and must be done through the direct observation of students performance in real situation.The present project aims to determine reliability and internal consistence of a tool to evaluate competences, in which a short observation (15 to 20 minutes) is done by a professor in the moment the student is working with a patient. After the end of the observation, the professor provides the student the feedback, showing the areas in which his performance was good and the ones he needs to improve. The evaluation of each competence: interview, physical exams, humanistic qualities, clinical judgement, skills for orientation, organization and general clinicalcompetence will be ranged in a scale from 1 to to 9, where 1, 2 and 3 are considered insuficient or insatisfactory, 4, 5 and 6, sufficient and 7 to 9 superior 12 videos were produced showing the students performance in helping inpatients at Pedriatic Nursery and Neonatal Care at the Clinical Hospital of UFMG, Brazil. These videos were watched, one by one, by 24 expert professors from the Pedriatic Department of Medical Faculty, of Minas Gerais, all of them with 28 years of experience and they ranged the Mini Clinical Evalulation Exercice (Mini-Cex) in competence components. The Intra Class Correlation Coefficient (ICC) was 0,708 with a reliableinterval of 95%, and the Cronbachs alfa Coefficient had a variation between 0,87 to 0,96 indicating good reliability and internal consistency of the instrument. The initial data suggests that Mini-Cex is a reliable tool and the studies must continue to determine its validity and feasibility.